Transforming end-of-life SWRO desalination membranes into nanofiltration membranes for the treatment of brackish water and wastewater - Anissa Somrani; Zaineb Mohamed; Kholoud Abohelal; Sara Larhrib; Noreddine Ghaffour; Maxime Pontié (Scientific Reports)
Abstract In this study, we explore the possibility of reusing end-of-life seawater reverse osmosis (RO) membranes to treat brackish water and industrial effluent. Prior to cleaning the end-of-life RO membranes, we conducted several autopsies in order to assess the extent of degradation. Based on these results, three cleaning protocols were tested and Ultrasil10 and/or chlorine solution were selected for further investigation. The cleaning capacity of the chlorine treatment at 4000 ppm.h was tested but proved inefficient as it leads to a denser cake and a significant decrease in hydraulic permeability. Therefore, we recommend commencing chemical cleaning with Ultrasil10 to remove foulants, thereby reconditioning the end-of-life RO membranes to meet nanofiltration membrane specifications. The cleaned end-of-life RO membranes exhibited enhanced hydraulic permeability (1.97 L·h⁻¹·m⁻²·bar⁻¹) and achieved a salt rejection of 85% for brackish water (6 g/L NaCl). With a molecular weight cutoff of 86 Da, these membranes effectively reduced brackish water conductivity to below 1000 µS/cm at 10 bars, complying with Tunisian drinking water standards (300–2500 µS/cm). Additionally, they demonstrated high efficiency in treating industrial effluents, achieving turbidity levels below 2 NTU and conductivity of 180 µS/cm. Operating at lower pressures, these membranes provided cost-effective, sustainable solutions and performed comparably to commercial new NF membranes, validating their potential for reuse in brackish water and wastewater treatment applications.